THE ARCHITECTURAL PRINCIPLES OF RAHMATAN LIL ALAMIN IN THE REALIZATION OF SUSTAINABLE ARCHITECTURE - Edrees, Munichy (Journal of Islam and Science, 2016)
Indonesian nation, with its majority of Muslim population, should implement its local wisdom that is derived from the Holy Qur'an and the Prophet’s Sunnah in managing the nation and the state. In this way, it will be explicitly capable of developing built environment model based on the principle of sustainable architecture as an introduction to the implementation of the principle of Rahmatan lil Alamin in architecture. This can be pursued by starting to awaken an appreciation of the practice of the Qur'an and the Prophet’s Sunnah in everyday life,  including in the employment of architecture. The theory of sustainable development is not a very popular concept among both the public and the architects themselves. Sustainable architecture is defined as a concept applied in architecture to support the sustainable concept, namely the concept of maintaining natural resources in order to last longer, which is associated with the vital potential life span of the natural resources and the ecological environment of human beings.  Allah reveals in QS ar-Rum/30 : 41“Mischief has appeared on lands and seas because of (the meed)  that the hands of man have earned, that (Allah) may give them a taste of some of their deeds: in order that they may turn back (from evil).”  Architects should have awareness about this subject in order that in conducting professional practice they always carefully pay attention to the natural environment so that the results of their design could provide a blessing for the environment. That is the true meaning of Rahmatan Lil Alamin.